DETERMINATION OF THE EFFICIENCY OF THE IMPROVED COTTON TOLASIN MOISTURE EQUIPMENT BASED ON EXPERIMENTS - М Ибрагимова; PhD. Ф. Исанов; М. Ахматов (American Journals, 2023)
In this article, on the basis of experiments, a model of the regression equation for the effective embedding of cotton fiber is analyzed.